Pengaruh Penggunaan Media Kotak Pintar Terhadap Kemampuan Membaca Pada Siswa Kelas I SD Negeri Kasongan - Olanda, Viona; Purnomo, Heru (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
This research seeks to assess the impact of using smart box media on the reading abilities of first-grade students at SD Negeri Kasongan. The research adopts a quantitative approach with a Quasi-Experimental Design method of the nonequivalent control group design type. The sample in this study was taken using a saturated sampling technique, consisting of two classes: class I A at SD Negeri Kasongan with 25 students as the experimental class using the smart box media and class I B at SD Negeri Kasongan with 25 students as the control class using PowerPoint media. The methods for data collection included observation, questionnaires, tests, and documentation. Data analysis techniques involved normality testing using the Shapiro-Wilk test, homogeneity testing using the F-test, hypothesis testing using the Independent Sample T-test, and effect size testing with SPSS 25. The study results indicated a significant improvement in students' reading abilities after using the smart box media. The experimental group had average pretest and posttest scores of 58.16 and 87.64, respectively, while the control group had scores of 58.84 and 70.68, respectively. Hypothesis testing was conducted at a significance level of 0.05. The analysis of posttest data using the independent samples test in IBM SPSS Statistics 25 yielded a value of 0.000 < 0.05, leading to the acceptance of H1 and rejection of H0. The effect size test indicated that the smart box media had a strong effect, with a value of 2.3. Therefore, it can be concluded that the smart box media positively impacts the reading abilities of Class I at students at SD Negeri Kasongan.